Optimization of Basic Teaching Skills of Islamic Education Students in the Kampus Mengajar Program - Defi Anita Listari; Muhammad Wildan Shohib (Journal of Islamic Education, 2025)
The purpose of this study was to explore in depth the profile of basic teaching skills of Islamic Religious Education students at the Muhammadiyah University of Surakarta and to find out how these students can optimize their basic teaching skills through the Kampus Mengajar program. This study used a qualitative method with a phenomenological approach. The researcher used semi-structured interviews and participant observation as primary data sources and documentation analysis as secondary data sources. The primary data sources were obtained through interviews with lecturers and several students who had completed the microteaching course and participated in the Kampus Mengajar program. The researcher used the interactive data analysis technique of Miles and Huberman, involving data reduction, data presentation, and concluding. The data validity technique used triangulation. Based on the results of the study, the profile of basic teaching skills of Islamic Religious Education students was in the very good category for the aspects of opening subjects, mastering the class, asking questions, closing lessons, explaining, and providing reinforcement. However, in the aspects of variation and small group discussions, students' skills were still quite adequate. In addition, students were able to maximize their basic teaching skills during the Kampus Mengajar program. Prospective student teachers who participate in the Campus Teaching program receive various significant opportunities and benefits that can contribute to the development of skills and financial support for teachers in general.